AESTHETIC EXPERIENCE AND AESTHETIC JUDGMENTS: THE FEATURES OF THE RELATIONSHIPS - Streltsov, Yaroslav I. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
The article examines the essence and relationship of aesthetic experience and aesthetic judgment. It is argued that philosophical aesthetics deals with constants that are fundamental to aesthetic experience. Such constants are phenomena and characteristics that have a fundamental ontological status in the aesthetic sphere. It was found that the ontological characteristic of aesthetic experience is that it is not reducible to “pure” rationality, that is, it is not something that is “adapted” to complete and final comprehension by the mind alone. Therefore, a complete “absorption” of aesthetic experience by a certain semantic structure is impossible: such experience always goes beyond any discursive boundaries and simultaneously opens them. In addition, aesthetic experience serves as one of the means of a person’s “contact” with the world and society. Forming on the material of sensations, aesthetic experience extends from the most general ideas about the universe to the inner life of a person. The analysis also showed that the formulation of an aesthetic judgment is based on the concepts of the perfect and the imperfect. In turn, the mastery of such concepts is carried out in the process of correlating a certain aesthetic fact with the existing value scale. That is why aesthetic judgments have signs of normativity. They also create the basis for a common worldview and attitude, lay the foundation for mutual understanding between people of a certain culture. The study showed that the process of aesthetic assessment is a constant correlation of the existing state of affairs with something ideal (within a certain value scale), this is a permanent “demand” for perfection, as well as a tireless search for an opportunity to fulfill this “demand”. At the same time, ethical experience is dissociated from “pure” pragmatics, which personifies vital necessity, because the aesthetic sphere is always associated with a certain “redundancy” in human existence. Also, the results obtained in the course of the study suggested that philosophical aesthetics, which takes into account and investigates the specificity of the phenomenon of corporeality, as well as such phenomena of human existence as affective sensitivity and sensitive rationality, is able to overcome the limitation of “an-esthetic” naturalism in aesthetics.